2023
DOI: 10.1371/journal.pone.0283641
|View full text |Cite
|
Sign up to set email alerts
|

Diverging trajectories of neighborhood disadvantage by race and birth cohort from childhood through young adulthood

Abstract: Prior research has established the greater exposure of African Americans from all income groups to disadvantaged environments compared to whites, but the traditional focus in studies of neighborhood stratification obscures heterogeneity within racial/ethnic groups in residential attainment over time. Also obscured are the moderating influences of broader social changes on the life-course and the experiences of Latinos, a large and growing presence in American cities. We address these issues by examining group-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…1 For example, because of durable inequality, disadvantaged families are often "stuck in place" (Sharkey, 2013) and lack the resources to move out of poor or high-crime neighborhoods. Considerable evidence points to the existence of stubborn path dependencies, especially neighborhood contextual disadvantages that are highly stable from childhood through adulthood (Candipan & Sampson, 2023;Timberlake, 2007). Childhood exposure to early neighborhood advantage is also linked to subsequent employment, educational, and income attainment (Chetty & Hendren, 2018) that feature in many theories of socioeconomic status and criminal behavior.…”
Section: Cumulative Processes and Racial Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 For example, because of durable inequality, disadvantaged families are often "stuck in place" (Sharkey, 2013) and lack the resources to move out of poor or high-crime neighborhoods. Considerable evidence points to the existence of stubborn path dependencies, especially neighborhood contextual disadvantages that are highly stable from childhood through adulthood (Candipan & Sampson, 2023;Timberlake, 2007). Childhood exposure to early neighborhood advantage is also linked to subsequent employment, educational, and income attainment (Chetty & Hendren, 2018) that feature in many theories of socioeconomic status and criminal behavior.…”
Section: Cumulative Processes and Racial Gapsmentioning
confidence: 99%
“…This argument is motivated by evidence showing the durable nature of multidimensional inequality by race. Neighborhood poverty is transmitted over generations and place (Sharkey, 2013), for example, and life-course research has shown the durable nature of both White privilege (Candipan & Sampson, 2023) and persistent Black disadvantage (Timberlake, 2007) in neighborhood environments. Upward intergenerational mobility at the individual and family level is also much lower for minority groups, especially for Blacks, than for Whites (Chetty et al, 2020).…”
Section: Racial Inequalities and Social Changementioning
confidence: 99%